2020
DOI: 10.3389/fevo.2020.574161
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Pangolin Demand by Understanding Motivations for Human Consumption in Guangdong, China

Abstract: Pangolins are some of the most trafficked mammals in the world. China is a major destination country for illegal wildlife trade and Guangdong Province is one of the areas of high domestic wildlife consumption. A willingness to consume lies at the root of the illegal wildlife trade. To understand the ideological roots of pangolin consumption, and to propose solutions, we conducted a consumption survey in 21 prefecture-level cities in Guangdong and have collected 1,957 valid questionnaires. In these questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…However, participants reported that there are no recent observations or records of pangolins in certain places where pangolins were sighted frequently 15 years ago. This is clearly linked to population declines resulting from overexploitation of habitat, extensive poaching and illegal trade (Nash et al, 2016; Trageser et al, 2017; Zhang et al, 2020). Illegal hunting (D'Cruze et al, 2018), habitat degradation (Gurung, 1996) and forest fires (Suwal et al, 2020) in these areas are considered to be the causes of declines in pangolin population and densities, which may have reduced the likelihood of pangolin sightings (Nash et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…However, participants reported that there are no recent observations or records of pangolins in certain places where pangolins were sighted frequently 15 years ago. This is clearly linked to population declines resulting from overexploitation of habitat, extensive poaching and illegal trade (Nash et al, 2016; Trageser et al, 2017; Zhang et al, 2020). Illegal hunting (D'Cruze et al, 2018), habitat degradation (Gurung, 1996) and forest fires (Suwal et al, 2020) in these areas are considered to be the causes of declines in pangolin population and densities, which may have reduced the likelihood of pangolin sightings (Nash et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the endemic primate species, the black snub-nosed monkey, holds significance in Tibetan Buddhism, where it is protected as it is believed to inhabit sacred mountains and must not be killed [24]. China demonstrates the high consumption of species as food, such as the Chinese pangolin, Malayan tiger, and François' langur, all known for their meat [16,25,26]. Bird species, like the helmeted hornbill, are also consumed in China and Malaysia, where wild birds are considered a delicacy [27].…”
Section: Categories and Utilization Of Wildlife In Asian Countriesmentioning
confidence: 99%
“…和 武 器 贩 卖 外 最 为 暴 利 的 犯 罪 活 动 之 一 (Wyatt, 2013;Nellemann et al, 2016), 正导致许多物种走向 灭绝 (Heinrich et al, 2019), 成为现今导致生物多样 性丧失的主要原因之一 (Mozer & Prost, 2023)。但由 于其极强的隐蔽性, 难以有效监管和监测, 给全球 生物多样性保护工作带来巨大挑战 (Broad et al, 2014;Challender et al, 2015)。 穿山甲(Manis spp. )是受非法野生动物贸易严 重影响的类群之一 (Challender et al, 2014a)。现存的 8种穿山甲广泛用于传统医药、食用和精神治疗 (Burgess et al, 2020)。 随着全球人口不断增长和社会 经济发展, 特别是在亚洲, 人们为改善健康状况, 对穿山甲甲片的药用需求持续增加 (Challender et al, 2020), 肉也从最初作为满足人类生存的一种传统 蛋白质来源, 转变为彰显消费者社会地位和备受猎 奇者追捧的一种美味 (Challender et al, 2014b;Zhang et al, 2020)。 而在北美, 人们则热衷于穿山甲皮革制 品的消费, 穿山甲皮靴、皮带和钱包等尤其受欢迎 (遇达祎等, 2001;Heinrich et al, 2016Heinrich et al, , 2017。由于对 穿山甲的旺盛需求, 2000-2019年间估计全球有超 过89.5万只穿山甲被贩卖, 使其成为全球贩卖最严 重的野生哺乳动物 (Challender et al, 2014a(Challender et al, , 2020Heinrich et al, 2017)。 全球多国对穿山甲甲片、肉和皮张的需求先是 造成中国国内种群下降 (Allen, 1938;王荣怀, 1985;遇达祎等, 2001;吴诗宝等, 2004a, 2005, 之后助长 了东南亚区域穿山甲的非法贸易 (吴诗宝等, 2005;Schoppe et al, 2020), 并逐渐蔓延至更远的非洲 (Challender et al, 2016;Heinrich et al, 2016)。当前, 中国已成为全球穿山甲走私贸易的主要目的地之 一 (Heinrich et al, 2017)。尽管中国政府在持续加强 对于野生动物保护的立法和执法力度 (Zhang et al, 2022a), 但每年仍有大量走私的穿山甲及其衍生物 被发现 (Zhou et al, 2014;Zhang et al, 2017;Ingram et al, 2019;Emogor et al, 2021)。因此, 在深入了解物 种消费和非法交易网络的基础上, 寻找针对性的有 效干预措施来保护穿山甲至关重要 (Challender et al, 2015;Patel et al, 2015; (Cheng et al, 2017;Zhang et al, 2017;…”
Section: 当前 野生动物非法贸易已成为除毒品、人口unclassified